Economical and Mathematical Impact on Planning Balanced and Nutritious Diet for Paralympic (Autistic) Athlete (100M Sprinter) Using Linear and Integer Programming Approach - Mohd Zailani, Natasha Amira; Howe, Lee Kah; Sufahani, Suliadi Firdaus (Research Center of Inorganic Materials and Coordination Complexes, FMIPA Universitas Sriwijaya, 2025)
Every athlete should maintain a balanced diet to ensure proper physical preparation before participating in any competition, as well as for recovery afterward. Dietary planning is essential for ensuring adequate nutrient intake and avoiding food allergens, which can help improve the condition of individuals with autistic (100M sprinter) athletes while also strengthening the immune system. Human dietary planning involves the use of strategies to select suitable food items that are healthy for the body and then integrate them into meals This paper seeks to use Linear programming and Integer programming to develop diet plans for autistic 100M sprinters aged 20-30years. Linear and Integer Programming are the two scientific approaches that can be useful in reducing the costs and considering some additional constraints such as the necessary amounts of certain nutrients, as well as the allergenic products that must not beused.